Wajah baru masyarakat Indonesia usai persentuhan antara Islam dengan budaya lokal sebagai sarana dakwah Islam di Indonesia: Kajian kritis Islam dan budaya lokal - Chumairo, Chumairo (Maliki Interdisciplinary Journal, 2023)
Indonesia is a country in Southeast Asia that is rich in diversity ranging from race, culture, religion, ethnicity, and so on. It is not surprising that its people have their own culture and traditions that are embedded in their hearts and make a difference. Especially the Indonesian people who initially believed in the animism-dynamism and Hindu-Buddhist belief systems. Seeing this phenomenon, it comes to mind for a moment that this diversity can be united with peace as Islam can melt with local culture without violence and coercion. The subtle touch of Islam to local culture succeeded in influencing the process of Islamization in Indonesia in terms of politics, religion, culture, social, arts, etc. so that Islam could be accepted easily and made Indonesia the largest Muslim majority population in the world. The cleverness and intelligence of preachers such as the walisongo succeeded in realizing acculturation between Islam and local culture. The success of the acculturation can be seen through traditions and cultures that are Islamic and still exist today such as the tradition of selametan, tahlilan, kupatan, maulidan, wayang kulit, and so on. In addition, Islam and local culture managed to become a unity that goes hand in hand and is inseparable like two eyes on a coin.